2021
DOI: 10.31219/osf.io/b5c8g
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relationship Satisfaction in the Early Stages of the COVID-19 Pandemic: A Cross-National Examination of Situational, Dispositional, and Relationship Factors

Abstract: The outbreak of the COVID-19 pandemic has had a large impact on various aspects of life, but questions about its effect on close relationships remain largely unanswered. In the present study, we examined changes in relationship satisfaction at the beginning of the COVID-19 pandemic by using a sample of 3,243 individuals from 68 different countries. Participants responded to an online survey that included questions about relationship aspects (e.g., shared time, housework division), special circumstances (e.g., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…Sixty-eight percent of girls spent less time with their partners since COVID-19 began, a change that was associated with worsening or mixed relationship quality. Romantic deprivation was most common among non-cohabiting participants who had not seen their partner in the last two weeks, supporting similar findings of prior studies among adults in high-or middle-income settings [16,25]. Together these results alert us to the consequences of social restrictions on romantic experiences of non-cohabiting youth.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Sixty-eight percent of girls spent less time with their partners since COVID-19 began, a change that was associated with worsening or mixed relationship quality. Romantic deprivation was most common among non-cohabiting participants who had not seen their partner in the last two weeks, supporting similar findings of prior studies among adults in high-or middle-income settings [16,25]. Together these results alert us to the consequences of social restrictions on romantic experiences of non-cohabiting youth.…”
Section: Discussionsupporting
confidence: 86%
“…Together these results alert us to the consequences of social restrictions on romantic experiences of non-cohabiting youth. An online study, including participants from 63 countries, mostly from the United States and Europe, found significant declines in relationship satisfaction among non-cohabitating partners due to decreased time together amid COVID-19 [16]. The consequences of social restrictions were magnified in our study's young population, including adolescents, which often entertains clandestine relationsdinteractions difficult to sustain while schools or social venues are closed due to the pandemic.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…We found few studies that have examined the impact of COVID-19 on intimate relationships and, in particular, how mechanisms of relationship support may have been affected. To generate data quickly, the majority of studies relied on convenience sampling (e.g., via social media; Balzarini et al, 2020;Lehmiller et al, 2021;Vigl et al, 2021), with consequent limitations on representativeness and generalizability. Studies have generally found that about half of participants experience a disruption to their sex-life quality, typically declines in frequency and satisfaction (Hensel et al, 2020;Vigl et al, 2021;Wignall et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…To generate data quickly, the majority of studies relied on convenience sampling (e.g., via social media; Balzarini et al, 2020;Lehmiller et al, 2021;Vigl et al, 2021), with consequent limitations on representativeness and generalizability. Studies have generally found that about half of participants experience a disruption to their sex-life quality, typically declines in frequency and satisfaction (Hensel et al, 2020;Vigl et al, 2021;Wignall et al, 2021). There has been less attention to intimate relationship quality; one international probability study found associations between COVID-related stress and greater conflict, mitigated by partner responsiveness (Luetke et al, 2020) but did not consider other key aspects of relationship quality such as support.…”
Section: Introductionmentioning
confidence: 99%